2011
DOI: 10.5114/aoms.2011.25560
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Helicobacter pylori infection in patients with common migraine headache

Abstract: IntroductionMigraine can cause headache in different communities so that 12-15% are suffering worldwide. Recently the relationship between infectious diseases such as Helicobacter pylori infection and migraine headache has been the focus of many studies. The current study was designed to evaluate IgG and IgM antibodies to H. pylori in patients suffering from migraine headaches.Material and methodsPatients who had diagnostic criteria for migraine were chosen as cases compared to some healthy individuals as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…Upper and lower GI diseases such as acid peptic disease, gastroesophageal reflux disease, inflammatory bowel disease, and constipation were previously shown to have a significant correlation with headache in the adult population (12)(13)(14)(15)(16)(17). On the other hand, in the pediatric population, only upper GI problems, such as acid peptic disease and abdominal pain, were shown to be related to headache (18)(19)(20). Abdominal migraine is a typical clinical feature of this association (21).…”
Section: Introductionmentioning
confidence: 99%
“…Upper and lower GI diseases such as acid peptic disease, gastroesophageal reflux disease, inflammatory bowel disease, and constipation were previously shown to have a significant correlation with headache in the adult population (12)(13)(14)(15)(16)(17). On the other hand, in the pediatric population, only upper GI problems, such as acid peptic disease and abdominal pain, were shown to be related to headache (18)(19)(20). Abdominal migraine is a typical clinical feature of this association (21).…”
Section: Introductionmentioning
confidence: 99%
“…This correlation has not been previously described in the pediatric population. However, the relationship between headache and upper GI problems, such as acid peptic disease and abdominal pain in the pediatric group, was previously described by multiple studies (18)(19)(20). Also, upper and lower GI conditions, such as acid peptic disease, gastro esophageal reflux disease, inflammatory bowel disease, and constipation have been shown to have a significant association with headache in the adult group (12).…”
Section: Discussionmentioning
confidence: 87%
“…Upper and lower GI diseases such as acid peptic disease, gastroesophageal reflux disease, inflammatory bowel disease, and constipation were previously shown to have a significant correlation with headache in the adult population (12)(13)(14)(15)(16)(17). On the other hand, in the pediatric population, only upper GI problems, such as acid peptic disease and abdominal pain, were shown to be related to headache (18)(19)(20). Abdominal migraine is a typical clinical feature of this association (21).…”
Section: Introductionmentioning
confidence: 95%
“…Other researchers have found a correlation between migraine and digestive disorders in adults. They found that approximately 75.7% of patients who had migraine also suffered from digestive disorders [reflux (47.1%), gastric ulcers (17.1%), and gastritis (4.3%)], and the prevalence of HP infection was 38.6% among them (26). The explanation of this phenomenon is that gastrointestinal neuroendocrine cells can synthesize and secrete 5-hydroxytryptamine, substance P, and vasoactive intestinal polypeptides.…”
Section: Discussionmentioning
confidence: 99%